Financial Sector Projections and Stress Testing in Financial Programming : A New Framework - Garcia Pascual, Antonio (IMF Working Papers; Working Paper, 2006)
This paper proposes a framework to check for consistency between the IMF's standard country surveillance tool, namely medium-term projections of the macroeconomic framework (including the real, fiscal, external, and monetary sectors), and the financial sector. Consistency here entails that the financial sector remain solvent in the medium term under the assumptions of the macroeconomic framework and that the macroeconomic framework is fine-tuned should threats to financial sector solvency arise as a result of assumptions underlying the medium-term macroeconomic framework projections. The proposed framework can also be used to conduct sensitivity analysis of the aggregated financial sector to various types of risks, including foreign exchange, interest rate, and credit risk. For surveillance purposes, this framework can easily be integrated into one of the standard sectoral files so that any update to the macroeconomic framework automatically feeds into the financial sector medium-term projections. We anticipate the proposed framework to be of interest to IMF economists as well as outside analysts.